Association of salivary Interleukin-6 levels in smokers with periodontitis - Ali, Alhussein M; Mohammed, Ayser N; Al-Waeli, Haider A; Al-Ani, Hadeer A (Journal of Baghdad College of Dentistry, 2024)
Background: Periodontal disease is caused by a combination of factors, with a plaque being the primary causative factor. Although periodontal bacteria play a significant contribution in the onset of periodontitis, the sustained inflammatory immune reaction, which is mostly directed by the elevation of pro-inflammatory cytokines, is the primary component responsible for tissue damage associated with periodontitis. Interleukin (IL)-6 is a pleiotropic cytokine, and it is released by a variety of cell types. IL-6 is crucial in the processes that lead to periodontal disease and has also been linked to the migration of inflammatory cells. Smoking is a key potential factor for periodontal disorders and is associated with an increase in both the onset and severity of periodontitis, this studay aims to assess the association between smoking cigarettes and the salivary levels of IL-6 in patients with periodontitis in comparison to healthy controls. Materials and Methods: The sample population consisted of seventy-four males, and they were separated into four different groups: a clinically healthy periodontium non-smoker group (n=12), a clinically healthy periodontium smoker group (n=12), a periodontitis non-smoker group (n=25) and a periodontitis smoker group (n=25). All of the participants’ saliva samples were taken, and then clinical periodontal parameters were looked at (plaque index, bleeding on probing, probing pocket depth and clinical attachment level). Biochemical analysis with an Enzyme-Linked Immunosorbent Assay (ELISA) was used to find out how much IL-6 was in the saliva. Results: The levels of IL-6 were found to be greater in the periodontitis groups compared to the control groups and in the smoking groups compared to the non-smoking groups. Most periodontal measures correlated significantly with IL-6 concentration in the saliva.Conclusion: This research revealed that smokers (both with and without periodontitis) have higher amounts of IL-6 in their saliva than nonsmokers (both healthy and periodontitis). This shows that smoking cigarettes had a boosting effect on the levels of IL-6 in the saliva.